An exploratory study of first-year accounting students’ perceptions on the socio-economic challenges of the transition to emergency remote teaching at a residential university - Ontong, J. M.; Mbonambi, S. (South African Journal of Higher Education, 2021)
For many higher education institutions, the emergency remote teaching (ERT) environment is unchartered territory. The move to ERT for residential universities during a pandemic has highlighted the necessity of understanding students’ needs in order to be able to successfully transition to an ERT environment. Performing an exploratory study, this study aims to identify possible socio-economic challenges to the ERT environment should another pandemic or an extended period of ERT take place. Using a questionnaire, this study obtained the perceptions of first-year accounting students regarding their adaptation to the ERT environment ERT. The findings suggest that a wide lens should be used when assessing residential university students’ adaptation to ERT. It appears that lecturers and the content offered may be quicker to adapt to the new learning environment; however, restrictions such as access to resources required for ERT may pose a significant obstacle to students engaging in ERT. The results of this study can be used by course planners to consider the impact of ERT on their students and further to potentially implement interventions or changes to their modules to create a larger area of inclusivity.